A escuta do colunismo feminino de Clarice Lispector em mulheres hoje: uma perspectiva da psicologia analítica - Santos, Antonieta Campos Serra Teixeira dos (2022)
This study is the result of a qualitative research that aimed to analyze the comprehension by women of nowadays of the feminine columns written by Clarice Lispector, through an approach in an experiential reading group from the perspective of Analytical Psychology. Three remote meetings were held with eight women between 25 and 35 years old, who had, at least, completed high school education, divided into two groups. Each meeting had a theme: (1) body and beauty; (2) love relationships and family formation; and (3) work. In the meetings, a woman's column was read and the participants discussed the theme based on the text. At the end of the discussions, two activities took place: (a) they were questioned about how they related to the proposed themes - the answers were written individually and shared, welcomed and discussed by the group; (b) in the last meeting, the participants, individually, reported what they considered to be symbols of what it is to be a woman today and, together, they constructed a phrase representing the chosen symbols and the discussions happened during the meetings. The results of (a) were categorized according to theme. The categories were formed from each main theme: for (1), external influences, selfacceptance, and notion of beauty; for (2), quality of love relationships, family influences, and self-knowledge and self-discovery; and, for (3), search for personal accomplishment, self-concept, difficulties imposed by the environment, and search for external validation. The results of (b) were analyzed symbolically. The participants were critical of several of Clarice's positions, but also pointed out signs of rupture by the writer. They reported, sometimes, behaving as the woman in the columns and facing prejudice and violence related to male chauvinism and the patriarchal culture, especially in romantic relationships. The results also indicate that the readings helped in the reflection and sharing of personal content and that the experiential groups can provide a safe psychological space for such sharing